Attention to online sales: The role of brand image concerns - Markus Dertwinkel-Kalt; Mats Köster (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We provide a novel intuition for why manufacturers restrict their retailers' ability to resell brandproducts online. Our approach builds on models of limited attention according to which pricedisparities across distribution channels guide a consumer's attention toward prices and lower herappreciation for quality. Thus, absent vertical restraints, one out of two distortions - a quality ora participation distortion - can arise in equilibrium. We show that, by ruling out both distortions,vertical restraints can be socially desirable, but can also hurt consumers through higher retail prices.Thereby, we identify a novel trade-off between efficiency and consumer surplus.
Keywords: D21; K21; L42; 330; Limited Attention; Online Sales; Antitrust; Vertical Restraints